AUTOIMMUNE DISORDERS IN WOMEN WITH TURNER SYNDROME AND WOMEN WITH KARYOTYPICALLY NORMAL PRIMARY OVARIAN INSUFFICIENCY - Bakalov, Vladimir K. (2012)
The higher prevalence of autoimmune diseases in women compared to men could be due to effects of ovarian hormones, pregnancy and/or the presence of a 2(nd) X chromosome. To elucidate the role of these factors, we investigated the prevalence and spectrum of autoimmune diagnoses in women with primary ovarian insufficiency associated with X chromosome monosomy (Turner syndrome, TS, n=244) and women with karyotypically normal (46,XX) primary ovarian insufficiency (POI, n=457) in a prospective study, conducted at the National Institutes of Health. We compared the study group prevalence to normative data for the U.S. population of women. Chronic lymphocytic (Hashimoto’s) thyroiditis (HT) occurred in 37% of women with TS vs. 15% with POI (P<0.0001); HT prevalence in both ovarian insufficiency groups significantly exceeded that in U.S. population of women (5.8%). Inflammatory bowel (IBD, 4%) and celiac disease (CD, 2.7%) were significantly increased in TS, but not in POI. No other autoimmune diagnosis, including Graves’ disease or Type 1 diabetes appears to be significantly increased in either group. Women with TS had higher pro-inflammatory IL6 and TGF β1 levels (p<0.0001 for both), and lower anti-inflammatory IL10 and TGF β2 levels (p<0.005 for both) compared to POI and to normal volunteers. Lifetime estrogen exposure and parity were significantly lower in TS compared to POI, which were in turn lower than the general population of women. The finding that lymphocytic thyroiditis is greatly increased in both women with TS and POI suggests that factors associated with ovarian insufficiency per se promote this form of autoimmunity. The absence of a normal second X-chromosome further contributes to increased autoimmunity in TS.